Beyond drug dealing: Developing and extending the concept of 'social supply' of illicit drugs to 'minimally commercial supply'. (April 2014) - Coomber, Ross; Moyle, Leah
<x xml:space="preserve">Abstract</x> A concept of 'social supply' has emerged in the UK that describes drug transactions that are almost exclusively to friends and acquaintances and that are non-commercially motivated. Social suppliers are increasingly understood not to be drug dealers 'proper' and many argue that the criminal justice system should consider and process them differently to commercially motivated suppliers. Recent (2012) changes to sentencing guidelines in England and Wales that have attempted to accommodate this will continue to struggle to deal with social supply however due to a continued reliance on how culpability is defined. This article explores the rationale for understanding social supply activities as a specific form of supply and a new (lesser) separate offence and also outlines a rationale for extending the concept to one of 'minimally commercial supply' something that explicitly accommodates the real-life circumstance of most supply transactions and is also inclusive of addicted user-dealers of heroin/other substances whom might reasonably be seen as closer to social suppliers than to drug dealers proper.